PENOLAKANJERMAN TERHADAP PERGANTIAN MADE IN GERMANY MENJADI MADE IN EU TAHUN (2010-2014) - MUhammad RIzki FIrzani; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains the rejection of Germany about the change of Made in Germany to be Made in European Union. The European Union as regional organization supranational oriented has power policy to make this organization exist in globalization era and can be through the financial crisis since 2008 untill 2015 well. European Commission gave proposal to European Parlement about new regular that every products are marketed in European Union must give the origin label where that products come from. Made in Germany is the most important label for every product that are produced in Germany. Besides, Made in EU is the new label created by Eropean Union 2004, purposed to support the economic integration of European Union overall. This research will explain the interest from European Union and the reason of Germany to maintain Made in Germany as its national label from its product. In this research will look the Regional Interest will collide with National Interest.Key words :Made in Germany , Rejection, Label, European Commission‟s Proposal, Interest